Manufacturing and friction welding of aluminium matrix composites – review of current status and future directions - Fuhaid, Mutlag Shafi; Krishnan, Pradeep Kumar; Maleque, Md. Abdul; Murali, R V; Ali, Mohammad Yeakub (The Mattingley Publishing Co., Inc, 2020)
Advancements in the manufacturing industries particularly in key areas such as new materials development, cost optimization of manufacturing methods and recycling methods of waste materials have been very important, significantly impactful and rapid. In the same direction, research efforts on metal matrix composites (MMC) such as aluminium matrix composites (AMC) are on the rise because of the fact that AMCs are widely used across various industries. The use of AMCs is limited by the type of fabrication methods followed, for example welding methods. AMCs have limitations towards fusion type welding processes. Solid-state welding (SSW) processes join dissimilar materials conveniently and may therefore overcome these limitations over fusion welding process. SSW processes have greater advantages such as effective joining, fumeless, reduced preparation time, environment friendly, etc. Friction welding (FW) is one of the SSW methods which work on the principle of generating thermal energy for welding operation by mechanical friction between a moving part and a stationary one. Friction stir welding (FSW) is another SSW process which is widely used for making dissimilar joints. FW process has proven to be more prospective and capable method than FSW for joining AMCs. Parameters such as mechanical strength, microstructure of the joint area, the behavior of the reinforcements during joining and more especially suitable production process for the preparation of MMC are very much important for consideration. In this paper, a comprehensive review of the research works done in the past on manufacturing of AMCs, alternate materials for constituent phases and use of FW for AMCs is discussed and findings analyzed to relate with the proposed research work. This review effort is very useful in order to carry out the research in the right direction after addressing the gap areas identified in the review.